2019
DOI: 10.1021/acssuschemeng.9b05424
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Methylaspartate Ammonia Lyase from E. coli O157:H7 for Efficient Asymmetric Synthesis of Unnatural Amino Acids

Abstract: The asymmetric addition of ammonia to unsaturated acids using engineered methylaspartate ammonia lyase (MAL) is a particularly attractive and atom-economic method for the synthesis of unnatural amino acids. However, owing to insufficient enzyme gene mining of MALs, the catalytic performances of MALs have only been characterized in a few organisms. Herein, we describe a novel MAL from Escherichia coli (E. coli) O157:H7, whose gene was derived from a genome mining strategy. The enzyme (designated as El-MAL) has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Based on our previous studies, we found that Ec MAL could accept a range of short-chain unsaturated carboxylic acids, including fumaric acid, mesaconic acid, and itaconic acid, for the asymmetric synthesis of unnatural amino acids (Ni et al 2020 ). However, Ec MAL showed low activity in the catalysis of bulky unsaturated carboxylic acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous studies, we found that Ec MAL could accept a range of short-chain unsaturated carboxylic acids, including fumaric acid, mesaconic acid, and itaconic acid, for the asymmetric synthesis of unnatural amino acids (Ni et al 2020 ). However, Ec MAL showed low activity in the catalysis of bulky unsaturated carboxylic acids.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, there was trace or even no specific activity observed for the WT. Moreover, compared with the bulky caffeic acid, different mutants exhibited obviously different catalytic activities (Ni et al 2020 ). Interestingly, the triple site mutant M6 showed significant improvement in activity toward 1b and was even better than M8 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Optically pure unnatural amino acids have emerged as a class of key building blocks for the synthesis of several fine chemicals, pharmaceuticals, agrochemicals, and pharmaceutically important peptides . Numerous biocatalytic routes employing wild-type or engineered enzymes, including acylase, aldolase, amidase, l - erythro -3,5-diaminohexanoate dehydrogenase, methylaspartate ammonia-lyase, aspartate ammonia-lyase, hydantoinase, lipase, nitrilase, amine dehydrogenase, imine reductase, monoamine oxidase, Baeyer–Villiger monooxygenase, and reductive aminase, have been developed to access chiral unnatural amino acids. Still, developing an efficient biocatalytic process for the synthesis of chiral β- and γ-amino acids remains a challenge …”
Section: Introductionmentioning
confidence: 99%